(untitled) - Pillari, Vimala (Pacific Grove, 1998)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Developmental psychology; Human behavior; Social ecology; Social psychology; Social service; Tâm lý học phát triển; Hành vi con người; Tâm lý xã hội; Dịch vụ xã hội